Production, characterization and techno-economic evaluation of Aspergillus fusant l-asparaginase - Atim Asitok; Maurice Ekpenyong; Andrew Amenaghawon; Ernest Akwagiobe; Marcus Asuquo; Anitha Rao; David Ubi; Juliet Iheanacho; Joyce Etiosa; Agnes Antai; Joseph Essien; Sylvester Antai (AMB Express, 2023)
Key points Sensitivity analysis confirmed optimization conditions for ATPS L-ASNase recovery Fed-batch fermentation outperformed other modes in techno-economic evaluations Fusant improved clinical and industrial characteristics indicate recombination success